Effect of the 2018 European drought on methane and carbon dioxide exchange of northern mire ecosystems. (26th October 2020) - Rinne, J.; Tuovinen, J.-P.; Klemedtsson, L.; Aurela, M.; Holst, J.; Lohila, A.; Weslien, P.; Vestin, P.; Łakomiec, P.; Peichl, M.; Tuittila, E.-S.; Heiskanen, L.; et al.
Abstract : We analysed the effect of the 2018 European drought on greenhouse gas (GHG) exchange of five North European mire ecosystems. The low precipitation and high summer temperatures in Fennoscandia led to a lowered water table in the majority of these mires. This lowered both carbon dioxide (CO2 ) uptake and methane (CH4 ) emission during 2018, turning three out of the five mires from CO2 sinks to sources. The calculated radiative forcing showed that the drought-induced changes in GHG fluxes first resulted in a cooling effect lasting 15–50 years, due to the lowered CH4 emission, which was followed by warming due to the lower CO2 uptake. This article is part of the theme issue 'Impacts of the 2018 severe drought and heatwave in Europe: from site to continental scale'.